2011
DOI: 10.1002/mop.25927
|View full text |Cite
|
Sign up to set email alerts
|

Design of high‐permittivity rectangular dielectric resonator antenna

Abstract: In this article, a high‐permittivity rectangular dielectric resonator antenna is proposed. In this configuration, wideband operation is achieved by loading a rectangular dielectric resonator on the center of the rectangular ring slot. Dielectric resonators of three different thicknesses have been studied. In this configuration, slot acts as an effective radiator and the feeding structure of the dielectric resonator. The dual‐band resonances of the two radiators, i.e., slot and dielectric resonator are combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…During this review process it has been also found some papers related to bandwidth by highlighting permittivity in their title. Mainly the effect of high permittivity on impedance bandwidth is discussed here . Mongia et al, have reported a high permittivity rectangular DRA ( ε r = 100) to achieve 3% impedance bandwidth.…”
Section: Dra Research On Bandwidthmentioning
confidence: 96%
See 2 more Smart Citations
“…During this review process it has been also found some papers related to bandwidth by highlighting permittivity in their title. Mainly the effect of high permittivity on impedance bandwidth is discussed here . Mongia et al, have reported a high permittivity rectangular DRA ( ε r = 100) to achieve 3% impedance bandwidth.…”
Section: Dra Research On Bandwidthmentioning
confidence: 96%
“…Broadly, these approaches can be divided into four categories; firstly, according to the antenna geometry (DR shape/fractal/EBG/metamaterial), secondly, the coupling mechanism (feeding type/aperture shape), thirdly, the DR permittivity, and lastly, according to the excitation of specific mode. From ease of readers' point of view, these techniques are discussed separately for single‐band, dual‐band, and multi‐band,, respectively. Moreover, some other characteristics say radiation/notch…”
Section: Dra Research On Bandwidthmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric resonator antenna (DRA) has attracted wide attention due to its advantages of high radiation efficiency, low conductor loss, easy excitation and high design flexibility 1–7 . More importantly, various modes of a single DRA element can be excited for diverse radiation characteristics 7–11 .…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of methods are reported in literatures for achieving reduced antenna size and obtaining more than one frequency band of operations. Some of the techniques involve using rectangular slotted patch [ 9 ], circular ring [ 10 ], defected ground plane [ 11 , 12 ], metamaterials [ 13 , 14 ], electromagnetic band-gap [ 15 ], high dielectric substrate [ 16 , 17 ], magnetodielectric material [ 18 ], fractal shape [ 19 , 20 ], split ring [ 21 , 22 ], various feeding techniques [ 23 25 ], stacked arrangement [ 26 , 27 ], and optimization technique like genetic algorithms [ 28 , 29 ]. None the less, still there is room for further development of techniques to enhance the design simplicity, flexibility of operations, and tunable functionality of multifrequency besides maintaining the desired antenna properties for the implementation of the compact wireless device.…”
Section: Introductionmentioning
confidence: 99%